Effect of electrodeposited Cu-Ni layer on interfacial reaction and mechanical properties of laser welded-brazed Mg/Ti joints / Auwal Shamsu Tukur - Auwal , Shamsu Tukur (2019)
The ability to join Mg alloys to Ti effectively has received great interest in the manufacturing sector, especially in automotive and aerospace industries where light weight components are crucial in order to exploit the advantages of both materials, reduce fuel consumption, greenhouse gases and improve performance of energy converting system. However, the significant differences in their physical and metallurgical properties make joining them together very difficult. Hence, selecting an appropriate welding technique and interlayer elements to produce and control interfacial layers became the focus of Mg/Ti joining. Based on the existing literature, controlling the heat input of welding parameter and the content of the interlayer elements were effective ways to regulate the interfacial reaction. In this work, 1.5 mm thick AZ31 Mg alloy was joined to 1 mm thick Ti-6Al-4V Ti alloy by laser welding-brazing process, using electrodeposited Cu-Ni layer under different welding schedules. Optical microscopy and scan electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS) were used to study the cross sectional microstructure morphologies and fracture surfaces. The reaction products formed was verified by X-ray diffraction (XRD) analysis. A test load of 100 g and 10 s dwell time were used to measure the Vickers hardness of the joints across the joint interface. In addition, room temperature tensile-shear test was performed on the 10 mm wide specimens machined from the joints with a cross head speed of 1 mm/min. Firstly, a fiber laser welding-brazing procedure has been developed for joining AZ31/Ti- 6Al-4V via electrodeposited Cu-Ni interlayer. The effect of the interlayer arrangements (AZ31/Ni-Cu/Ti-6Al-4V and AZ31/Cu-Ni/Ti-6Al-4V) on appearance, interfacial reaction and mechanical properties were investigated at different heat input. The results showed that the feasibility of the process significantly depend on the pre-existing Cu-Ni layer on the Ti surface that facilitates wetting of AZ92 brazing alloy. Depending on the interlayer arrangements chosen, different reactions layers formed inside the joint region. Nevertheless, at optimum heat input Ti2Ni mingled with Ti3Al interfacial reaction products was produced along the fusion zone (FZ)-Ti brazed interface in both interlayer arrangements, which grew evidently with increase in heat input. The average joint efficiency of 71% compared to AZ31B alloy was achieved. Under suitable heat input, the joints failed at the fusion zone of the AZ31B base metal, whereas, incomplete brazing or large volume of intermetallics at the brazed interface resulted in interfacial failure at lower/higher heat input. Secondly, the effect of the Cu and Ni contents on microstructure development and joint fracture load was analyzed. The results showed that the joining mechanism between the Mg alloy and the Ti was facilitated by the formation of a Ti2Ni and Ti3Al mixed interfacial reaction layer formed along the fusion zone-Ti brazed interface. However, the actual interfacial products were influenced by the welding method and interlayer elements content. At optimum Cu and Ni contents, the thickness of this mixed interfacial reaction layer was less than the critical thickness of 10 µm. The maximum tensile-shear fracture load attained 2020 N, which was about 100% higher than that of the uncoated joint. Finally, the relationships between interface characteristics, joint formation mechanism and mechanical properties of Mg/Ti joint with and without Cu, Ni and Cu-Ni coatings have been investigated and the Cu-Ni coated joint presented superior mechanical performance.